2003
DOI: 10.1038/sj.ijo.0802482
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the thermogenic nuclear hormone receptor coactivator PGC-1α is reduced in the adipose tissue of morbidly obese subjects

Abstract: Peroxisome proliferator-activated receptor gamma coactivator 1a (PGC1a) is an accessory protein which can potentiate the transcriptional activation function of many nuclear hormone receptors. Its tissue distribution and physiological studies suggest that its principal in vivo roles are to promote cold-induced thermogenesis, mitochondrial biogenesis, hepatic gluconeogenesis, and fatty acid b-oxidation. It is expressed in the white adipose tissue of both humans and rodents, and in rodents it has been suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
117
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(136 citation statements)
references
References 17 publications
14
117
2
3
Order By: Relevance
“…Individuals with type 2 diabetes exhibit reduced PGC-1α gene expression in adipose tissue (25,26). Whether this downregulation is a consequence of the disease or actively contributes to disease pathogenesis has not been clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with type 2 diabetes exhibit reduced PGC-1α gene expression in adipose tissue (25,26). Whether this downregulation is a consequence of the disease or actively contributes to disease pathogenesis has not been clear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reduced adipose PGC-1α and an association between reduced PGC-1α mRNA levels and insulin resistance have been found in human subjects (25,26). Adipose mitochondria play an important role in fatty acid oxidation (FAO) and adaptive thermogenesis, key adipose-specific metabolic pathways that are regulated by PGC-1α (27).…”
mentioning
confidence: 99%
“…125 PGC1A is expressed at low levels in human adipose tissue and mRNA levels are reduced in morbid obesity. 126,127 SNPs in the PGC1A gene have been reported to be associated with obesity in Austrian women. 128 PPARG coactivator 1B (PGC1B) is a recently discovered homologue of PGC1A, which, like PGC1A, in experimental animals induces expression of genes involved in oxidative phosphorylation.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%
“…The expression of the master regulator of mitochondriogenesis, peroxisome proliferator-activated receptor-coactivator-1a (PGC-1a), has been reported to be reduced in adipose tissue from obese patients. 26 Other authors found a downregulation of expression of mitochondrial electron transport (OXPHOS) genes preferentially in visceral adipose tissue of obese patients developing type 2 diabetes. 27 In mice, weight gain has been associated with the downregulation of OXPHOS genes in visceral adipose tissue, 28 and in ob/ob mice, an animal model of obesity, there is reduced mtDNA in visceral adipose tissue.…”
Section: Introduction: Overview Of Adipose Tissue Disturbances In Hivmentioning
confidence: 99%